SOSIAL BUDAYA DAN EKONOMI PENGOLAH IKAN ASAP DI BANDARHARJO KOTA SEMARANG - Widayatsih, Tri (Jurnal Ilmu-Ilmu Perikanan dan Budidaya Perairan, 2014)
System of social, culture and ecomonics produce many problem in society, the one of be must be concern is poverty. Poverty didnât solving can disturb everything aspect for the rest of they life. Study to observe caused problems of poverty with appropriating from social cultural and economic system is very important. Poverty can be solving with structural and cultural aspect, in this situation the role from goverment is very important as holding policy and power to produce strategy and law.Keywords : Culture, Economics and Social